Algorithmic Uncertainty: Adaptive Coping Strategies Sustaining Delivery Drivers’ Psychological Well-Being - Mohamad Imam Fauzi; Fandu Dyangga Pradeta; Qomaruzzaman Azam Zami (Journal of Psychological Insight, 2026)
The rapid growth of digital platform-based transportation has created flexible employment opportunities while simultaneously increasing job uncertainty that affects workers’ psychological well-being and quality of life. This study aims to analyze the social resilience mechanisms that online delivery drivers develop to cope with job uncertainty. A qualitative descriptive design was applied using purposive sampling, involving three active drivers with at least 1 year of work experience. Data were collected through in-depth interviews, field observations, and documentation, and analyzed using the interactive model of data condensation, data reduction, data display, and verification. The findings show that income instability generates psychological pressure and anxiety among drivers, while adaptive coping strategies such as monitoring delivery applications and managing waiting time help maintain work continuity. In addition, peer support through information sharing and emotional encouragement strengthens drivers’ collective resilience. This study contributes to understanding social resilience as a psychological and social mechanism within digital platform labor environments and highlights the importance of strengthening worker support networks.